2004
DOI: 10.1097/01.sla.0000124447.30808.c7
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Submucosa for Vascular Reconstruction in the Presence of Gastrointestinal Contamination

Abstract: SIS was associated with improved graft patency, less infection, complete incorporation, and no false aneurysm formation when compared with PTFE. This may be due to its ability to provide a durable scaffold for cellularization and tissue remodeling. This material may offer a superior alternative to more complex vascular reconstruction techniques in contaminated fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 33 publications
1
50
1
Order By: Relevance
“…It is plausible that such cells would then differentiate in response to local environmental cues, and thus contribute to tissue organization and differentiation. It has also been shown that degradation products of SIS-ECM have an antimicrobial effect, [35][36][37][38] and that without ECM degradation this effect is not observed. 39 Factors that inhibit the ECM degradation process, such as chemical crosslinking, may interfere with the biological activities that have been demonstrated by the products of ECM degradation.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that such cells would then differentiate in response to local environmental cues, and thus contribute to tissue organization and differentiation. It has also been shown that degradation products of SIS-ECM have an antimicrobial effect, [35][36][37][38] and that without ECM degradation this effect is not observed. 39 Factors that inhibit the ECM degradation process, such as chemical crosslinking, may interfere with the biological activities that have been demonstrated by the products of ECM degradation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Such biological scaffolds have been surprisingly resistant to bacterial infection, [13][14][15][16] even in clinical applications that are at high risk for bacterial contamination. [17][18][19][20] Generally, naturally occurring biomaterials such as those composed of purified collagen or intact ECM are more resistant to bacterial infection than synthetic biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…iologic scaffolds composed of extracellular matrix (ECM) can promote the constructive remodeling of injured tissues through mechanisms that include angiogenesis, [1][2][3][4][5] the recruitment of multipotential progenitor cells to the site of tissue reconstruction, [6][7][8][9] the release of antimicrobial peptides, [10][11][12][13][14][15] and activation of the alternative pathway of immunity. [16][17][18][19][20] There is convincing evidence that hostmediated degradation of ECM scaffolds is typically completed within 8-12 weeks and is necessary to realize the full beneficial effects of ECM-mediated tissue remodeling, [21][22][23] but the mechanisms by which such scaffold degradation occurs have been largely ignored.…”
mentioning
confidence: 99%